2021
DOI: 10.3390/buildings11110556
|View full text |Cite
|
Sign up to set email alerts
|

Towards Meaningful University Space: Perceptions of the Quality of Open Spaces for Students

Abstract: This study investigated students’ attitudes towards the use of outdoor open space in universities, identifying the most comfortable conditions and favourable factors, including urban layout, physical features, and outdoor thermal conditions, as well as the students’ needs and behaviour. A quasi-experiment was used to assess the quality of the outdoor spaces. Three outdoor open spaces on the university’s campus were used for the case study. A spatial analysis employing space syntax was used to determine the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…showed that (49.2%) of them believe that garden maintenance is average and (27.9%) see garden maintenance as poor. Through our frequent visits and meetings with maintenance officials, the college administration is interested in garden maintenance, but the problem is the lack of elements Plant and construction that need maintenance, the green surface is damaged, except for some important areas that lie before the eyes of visitors * The college administration has provided the requirements and machines for maintenance operations in a good way, and the number of maintenance workers is 24 workers, and this number is suitable for the area of the college's gardens, as it has an area of 6 and a half dunums.• The results of the questionnaire showed, as indicated in Table (5), that (63.7%) believe that the wide open green spaces are not sufficient, and this is what we noticed in the university.• The results of the questionnaire showed, as shown in Table(6), that 62.1% of the students are attracted by various natural elements such as trees, shrubs, flowers, etc., and this is due to man's attachment to nature and his presence in abundance in his life, although the percentage of structural elements are complementary to gardens and their importance, such as benches and fountains Monuments, statues...etc.• The results showed, as indicated in TableNo. (…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…showed that (49.2%) of them believe that garden maintenance is average and (27.9%) see garden maintenance as poor. Through our frequent visits and meetings with maintenance officials, the college administration is interested in garden maintenance, but the problem is the lack of elements Plant and construction that need maintenance, the green surface is damaged, except for some important areas that lie before the eyes of visitors * The college administration has provided the requirements and machines for maintenance operations in a good way, and the number of maintenance workers is 24 workers, and this number is suitable for the area of the college's gardens, as it has an area of 6 and a half dunums.• The results of the questionnaire showed, as indicated in Table (5), that (63.7%) believe that the wide open green spaces are not sufficient, and this is what we noticed in the university.• The results of the questionnaire showed, as shown in Table(6), that 62.1% of the students are attracted by various natural elements such as trees, shrubs, flowers, etc., and this is due to man's attachment to nature and his presence in abundance in his life, although the percentage of structural elements are complementary to gardens and their importance, such as benches and fountains Monuments, statues...etc.• The results showed, as indicated in TableNo. (…”
mentioning
confidence: 75%
“…It is considered an important and influential element in the design of universities of all kinds, as it contributes to providing an appropriate university environment, whether it is scientific, recreational, or service for students or users of these spaces, in addition to its role in linking the parts of the university together and facilitating movement from one place to another inside. The university includes:  Gardens  Parking lots  walkways  sports stadiums  Paved yards (6). Definition (green spaces ): It is considered an area of space located in a place where the natural element dominates, such as natural parks or forests, either it is prepared according to a previously prepared design, as in gardens and public parks, and it is also considered covered with plants, whether in whole or in part.…”
Section: External Spacesmentioning
confidence: 99%
“…The COVID-19 crisis is likely having long-lasting effects on people, and thus a precise understanding of the pandemic's psychological impact is needed. The features of the built environment shape human behavior [83]. Therefore, when planning and designing cities, there is a need to address the psychological impact of COVID-19 on people.…”
Section: Human Psychology and The Pandemicmentioning
confidence: 99%
“…Such friendly interaction can also be applied to remote health monitoring services for the elderly, providing sustainable and innovative service experiences. In addition, a study [45] of students' attitudes toward the use of outdoor space on university campuses found that some students' educational experiences depend on good campus design. The visual factor and spatial configuration of a campus site can provide the most comfortable campus environment.…”
Section: User Experiencementioning
confidence: 99%